Sustainable value chain management : delivering sustainability through the core business - D'heur, Michael (Cham : Springer Verlag, 2015)
This book introduces the integrated management concept of "Sustainable Value Creation", which delivers sustainability `inside-out' from the core business. What are the practical examples of sustainable value chains in leading companies that can inspire others to follow?
Includes bibliographical references.
oif 07/12/2017
Loans
Keywords: Business logistics --Management.; Social responsibility of business; Value chain